KONTRIBUSI PEMBELAJARAN MENGGUNAKAN MEDIA BERBASIS KOMPUTER DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR MATA DIKLAT PERAWATAN CHASIS DAN PEMINDAH TENAGA SISWA KELAS XI PROGRAM KEAHLIAN TEKNIK KENDARAAN RINGAN SMK MUHAMMADIYAH 3 YOGYAKARTA TAHUN PELAJARAN 2012/2013 - Adi Kristanto; Pairun Roniwijaya (Jurnal Taman Vokasi, 2013)
Research this intent to know contribution Learning Utilize Media Get basis Computer and Learned motivation to Achievement Subject studying PCPT Student brazes XI Majors Tech Vehicle Demulcent sMK Muhammadiyah 3 yogyakarta. Research this are research expost facto. Population in this research are student braze XI majors Tech Vehicle Demulcent SMK Muhammadiyah 3 Yogyakarta one that total 140, meanwhile its sample total 115 student that pointing nomogram Harry King, sample take in observational it utilize propotionate random is sampling. Observational result this point out that: Contribution Relative Learning Utilize Media Get basis Computer as big as 33,020, Contribution Relative Learned motivation as big as 66,98%, contribution Effective learning Utilize Media Get basis Computer as big as 17,09%, Contribution Effective Motivation berlajar as big as 34,66%.